FAMILY HOPE PROGRAM (PKH) EXTENSION WORKERS' EFFORTS IN ALLEGING POVERTY IN THE COMMUNITY IN KALIWUNGU SUB-DISTRICT, KENDAL REGENCY - Nihayah, Ulin; Wijayanti, Lina (Universitas Islam Negeri Raden Intan Lampung, 2022)
Poverty remains a major issue in Indonesia. One of the government's efforts to alleviate poverty is the Family Hope Program (PKH). This study aims to describe the Extension Workers' efforts in implementing the Family Hope Program (PKH) to combat poverty in Kaliwungu District, Kendal Regency. Among the outcomes of the efforts made is 1. Socialization of the distribution of assistance through the provision of materials, business training, and assistance in resolving various problems in the field. 2. Increasing the group's economy through skill-based activities such as business partners. 3. Changes in behavior (knowledge, attitudes, and skills) where being in chronic poverty becomes temporary poverty because KPM (Benefit Recipient Families) has acquired business skills. 4. Empowerment of the Independent Community through Skill Training Activities such as making bags and brooches out of cloth that will later be made into saleable goods for the beneficiary families.